Beyond the story : 10-year record of BTS - Kang, Myŏng-sŏk (Flatiron Books, 2023)
"After taking their first step into the world on June 13, 2013, BTS will celebrate the 10th anniversary of their debut in June 2023. They have risen to the peak as an iconic global artist and during this meaningful time, they look back on their footsteps in the first official book. In doing so, BTS nurtures the power to build brighter days and they choose to take another step on a road that no one has gone before. BTS shares personal, behind-the-scenes stories of their journey so far through interviews and more than three years of in-depth coverage by Myeongseok Kang, who has written about K-pop and other Korean pop culture in various media. Presented chronologically in seven chapters from before the debut of BTS to the present, their vivid voices and opinions harmonize to tell a sincere, lively, and deep story. In individual interviews that have been conducted without a camera or makeup, they illuminate their musical journey from multiple angles and discuss its significance"--